PELATIHAN KRIYA ULOS BAGI WARGA BINAAN KELAS IIB TARUTUNG - Damayanti Br Hombing (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACT The ulos craft training for inmates at Class IIB Tarutung Detention Center is conducted as a means of fostering self-reliance and developing productive skills necessary for supporting their reintegration into society. This program is designed to support inmates who lack vocational skills aligned with the cultural heritage of the region, with a particular focus on the traditional Tapanuli ulos fabric. The training was implemented using a participatory approach, encompassing needs mapping, demonstration of basic weaving techniques, guided practice, and assessment of outcomes. The findings indicated an improvement in the participants' technical skills in using ulos craft tools, understanding basic patterns, and producing initial works such as tandok. This training has had a positive impact on the enthusiasm, motivation, and self-confidence of the inmates. This training makes an important contribution to fostering independence and opens up potential employment opportunities after the completion of the incarceration period. Kata Kunci : Training, Ulos Craft, Inmates ABSTRAKPelatihan kriya ulos bagi warga binaan di Rutan Kelas IIB Tarutung dilakukan sebagai bentuk pembinaan kemandirian sekaligus pengembangan keterampilan produktif yang diperlukan untuk mendukung proses kembali mereka ke masyarakat. Kegiatan ini bertujuan membantu warga binaan yang tidak memiliki kemampuan kerja sesuai dengan kekayaan budaya daerah, khususnya warisan kain ulos Tapanuli. Pelatihan diterapkan melalui pendekatan partisipatif, mencakup pemetaan kebutuhan, demonstrasi teknik dasar menenun, praktik terarah, serta penilaian hasil. Temuan menunjukkan adanya peningkatan keterampilan teknis peserta dalam menggunakan alat kriya ulos, memahami pola dasar, dan menghasilkan karya awal seperti, tandok. Pelatihan ini memberikan dampak positif terhadap semangat, motivasi dan rasa percaya diri warga binaan. Pelatihan ini memberikan kontribusi penting bagi pembinaan kemandirian dan membuka potensi peluang kerja setelah masa tahanan berakhir.Kata Kunci: Pelatihan, Kriya Ulos, Warga Binaan